New country records for Neotropical Cerambycidae (Insecta: Coleoptera) - Gino Juárez-Noé; Christoffer Fägerström (Revista Chilena de Entomología)
Based on the examination of Cerambycidae material deposited in the entomological collection of the Biological Museum of Lund University (Sweden), new country records are provided for Pronuba incognita Hovore & Giesbert, 1990 (Colombia), Eriphus bisignatus (Germar, 1824) (Paraguay), Stenolis inclusa (Bates, 1885) (Colombia), Aegomorphus bivittus (White, 1855) (Suriname), Colobothea emarginata (Olivier, 1795) (Paraguay), Colobothea chemsaki Giesbert, 1979 (Colombia), and Colobothea plebeja Aurivillius, 1902 (Brazil). Additionally, a new state record for Colobothea seriatomaculata Zajciw, 1962 (Brasilia, Brazil) is provided.